2020
DOI: 10.1177/2055102920973253
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and suicidal ideation among Vietnamese students aged 13–17: Results from a cross-sectional study throughout four geographical regions of Vietnam

Abstract: We conducted a cross-sectional study in four provinces located in four different geographical areas in Vietnam to examine the prevalence and associated factors of depression and suicide ideation among school students aged 13–17. A sample of 6407 students from secondary school and high school participated in our survey to complete self-reported questionnaires. Depressive symptoms were measured by the Center for Epidemiologic Studies Depression scale (CES-D). Suicidal ideation and associated factors were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
8
0
5
Order By: Relevance
“…The research results of Hansson et al (2020) showed that the experience of being a victim of bullying in adolescents can increase the risk for depression by 3.84 times greater than adolescents who have never been victims of bullying (95%CI= 3.13 to 4.71). Similarly, the research of Tran et al (2020) which showed that the experience of bullying in adolescents can increase the likelihood of adolescents experiencing various depressive symptoms (OR= 1.30; 95%CI= 1.10 to 1.50), and women have a higher likelihood of experiencing depression than men. In addition, the research of Wilson et al (2012) also showed that the experience of bullying has the potential to increase the incidence of depression in adolescents by 1.63 times (95% CI = 1.27 to 2.09).…”
Section: The Effect Of Bullying On Depressionmentioning
confidence: 74%
“…The research results of Hansson et al (2020) showed that the experience of being a victim of bullying in adolescents can increase the risk for depression by 3.84 times greater than adolescents who have never been victims of bullying (95%CI= 3.13 to 4.71). Similarly, the research of Tran et al (2020) which showed that the experience of bullying in adolescents can increase the likelihood of adolescents experiencing various depressive symptoms (OR= 1.30; 95%CI= 1.10 to 1.50), and women have a higher likelihood of experiencing depression than men. In addition, the research of Wilson et al (2012) also showed that the experience of bullying has the potential to increase the incidence of depression in adolescents by 1.63 times (95% CI = 1.27 to 2.09).…”
Section: The Effect Of Bullying On Depressionmentioning
confidence: 74%
“…Our study also unveiled an exceptionally high prevalence of depression among Vietnamese students, compared to other recent domestic studies. For example, depression rates reported in two former studies in Vietnam by Nguyen, Dedding & Pham (2013) and Tran, Le & Nguyen (2020) were 41.1% and 37.1%, respectively. Regarding similar studies in the world on adolescents using the same measurement questionnaire, our study found an even higher prevalence.…”
Section: Discussionmentioning
confidence: 91%
“…Another study of 6,407 students found that 31.7% of students experienced depression. Noticeably, traditional bullying was found to be a significant risk factor of depression among students ( Tran, Le & Nguyen, 2020 ). Ho Chi Minh City is one of the most important economic, political, cultural, and educational centers in Vietnam ( People’s Committee of Ho Chi Minh City, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent cross-sectional study among students aged 13–17 from four different geographical locations in Vietnam found that female students and older students had a higher risk of experiencing depressive symptoms than younger male students [ 46 ]. Another cross-sectional study among the Danish general population also found that females were more likely to have depression [ 47 ]. For gender, one explanation may be that gender roles in Chieng Sai are more equally distributed in society, with men and women both occupying prominent roles.…”
Section: Discussionmentioning
confidence: 99%